O coronel e o lobisomem nas veredas da literatura regionalista brasileira - Moreno, Naiara Alberti [UNESP] (2014)
This research aims to analyse the novel The Colonel and the Werewolf, by José Candido de Carvalho, published in 1964. The work puts in question the concept of literary regionalism within Brazilian literature, in order to inquire if this novel can be considered part of the superregionalist tendency. With regards to this, we try to determine the place that the novel occupies both within the production of Jose Candido, as well as within the entire genre of Brazilian regionalist literature. The starting point is the hypothesis that The Colonel and the Werewolf figures as an illustration of a transformation process that occurred in Brazilian literature, by which the regionalist novel becomes a narrative related to mythical and popular models. The study of super-regionalism (the critical category) requires the understanding of other concepts such as narrative transculturation, which will also be scaled down to contribute to the reading of the regionalist narrative in its unusual dimension. From this phenomenon on, we can outline the author's career, in order to contribute for the revision of critical studies about José Cândido and to increase understanding of the paradigms which characterized the Brazilian literary regionalism